Mediating Effect of Technological Enablement on Entrepreneurial Adoption among Students in Higher Education: A Confirmatory Analysis of Technological Enablement Entrepreneurial Model (TEEM) - Keoy, Kay Hooi; Koh, Yung Jing; Chit, Su Mon; Kwek, Choon Ling; Genaro, Japos; Lee, Luqman; Thong, Chee Ling (International Business Education Journal, 2022)
With the advent of the COVID-19 pandemic, students at higher education institutions have recently relied greatly on technological support for their studies and remote support from their universities. Technological enablement is a major determinant of entrepreneurial initiation among higher education students in Malaysia. Empirical studies demonstrate the growing interest in investigating the impact of entrepreneurship education on entrepreneurial success among the country’s higher education students. The focus areas include how governmental support, entrepreneurial intention, entrepreneurial education, and technological enablement (mediator factor) can influence entrepreneurial initiation. Therefore, this study aims to determine the factors that affect entrepreneurial initiation (action) among graduating students and the mediating effect of technological enablement on entrepreneurial adoption among students at higher education institutions in Malaysia. The study used Google Form to obtain information related to the topic. Data collection from 297 students in Peninsular Malaysia was voluntary and based on informed consent and anonymity. PLS-SEM (partial least squares structural equation modeling) with a formative-reflective model was adopted to assess the direct and indirect effects alongside the mediating factor. Hence, Smart PLS software was adopted for data analysis. Empirical results also proved that technological enablement as a mediating factor has a greater and significant impact on perceived entrepreneurial success. The results empirically demonstrate that the technological enablement factor has a major impact and influence when students at higher education institutions start businesses. Through such findings, policymakers at the institutional level will be able to identify and deliver the technological support and initiatives necessary to achieve a higher rate of entrepreneurial adoption success.